The pawn who refused - Stein, William W. (1974)
When the Cornell — Peru Project took over the Vicos hacienda in January 1952, the terms of the Contract called for the continuation of the hacienda system; so that as some experimental reforms were implemented during the five years in which the members of the Project acted as bosses, the hacienda workers were left under certain traditional conditions of control. The project itself consisted of a far-reaching attempt, both to carry out certain reforms in the Vicos community, and to contribute to a better understanding of socio-cultural change.